African designs from traditional sources - Williams, Geoffrey (Dover pictorial archive series, 1971)
These 378 linocut prints in_crisp black-and-white_designs reflect traditional_work from Zulu, Masai, and dozens of other tribes. This pictorial archive includes masks, abstract motifs, and much more.